Perturbation and Stability of Continuous Operator Frames in Hilbert C∗-Modules. (16th June 2021) - Touri, Abdeslam; Labrigui, Hatim; Rossafi, Mohamed; Kabbaj, Samir
Abstract : Frame theory has a great revolution in recent years. This theory has been extended from the Hilbert spaces to Hilbert C ∗ -modules. In this paper, we consider the stability of continuous operator frame and continuous K -operator frames in Hilbert C ∗ -modules under perturbation, and we establish some properties.